ANALISIS PERKEMBANGAN BAHASA PADA ANAK USIA SMP PEMAIN GAME ONLINE ANDROID BERGENRE BATTLE ROYALE - Gugun Gunawan; Helmi Aziz (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2018)
The purpose of this study was to determine the language development of junior high school aged children who became players of the online android game battle royale genre. The method used in this research is descriptive qualitative method, which is a method that describes an objective state or certain event based on visible facts or as it should be, which is then accompanied by general conclusions based on these historical facts. The results obtained from this study are that there are various vocabularies that appear, develop, master, and become a special communication language by junior high school students when they play online games. The vocabulary is an uptake and modification of the 3 main languages, namely English, regional languages, and Indonesian. However, based on its meaning, most of the vocabulary used is negative or harsh. This triggers the development of language and character of students who are not good, especially in the family and school environment. Therefore, intensive supervision from parents is needed and strong regulation from the government through the education office regarding the use of the Android online games in the battle royale genre